1998
DOI: 10.1246/cl.1998.579
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Diffuse Reflectance Spectroscopy of Aqueous Titanium(IV) Oxide Suspension: Correlation of Electron-Hole Recombination Kinetics with Photocatalytic Activity

Abstract: Pump-probe diffuse reflectance measurements were carried out on particulate titanium(IV) oxide photocatalysts in the form of aqueous suspension and dry powder. A linear relation between second-order rate constants of electron-hole recombination for the suspension and powder systems was seen by analyses of decay profile of charge carriers. Presence of air gave negligible effect on the recombination kinetics, but loading of platinum (Pt) significantly reduced the rate constant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
105
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 7 publications
3
105
2
Order By: Relevance
“…As discussed later, the coefficient may be related to the intrinsic activity of TiO 2 , that is, the e --h + recombination kinetics of each TiO 2 sample. In a previous paper, 63 we investigated the recombination kinetics after photoexcitation by femtosecond pump-probe diffuse reflectance spectroscopy and found that the second-order rate constant for e --h + recombination in HyCOM-B(unc) was 1.3-1.5 times smaller than that in P-25, which is consistent with the difference in the coefficients in this study. Figure 3b shows r(CO 2 ) by the calcined HyCOM-B powders.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As discussed later, the coefficient may be related to the intrinsic activity of TiO 2 , that is, the e --h + recombination kinetics of each TiO 2 sample. In a previous paper, 63 we investigated the recombination kinetics after photoexcitation by femtosecond pump-probe diffuse reflectance spectroscopy and found that the second-order rate constant for e --h + recombination in HyCOM-B(unc) was 1.3-1.5 times smaller than that in P-25, which is consistent with the difference in the coefficients in this study. Figure 3b shows r(CO 2 ) by the calcined HyCOM-B powders.…”
Section: Resultssupporting
confidence: 90%
“…57 Such dependence of r(Ag) on C ads (Ag + ) was first reported, to the best of our knowledge, by Fleischauer and co-workers 64 and recently by Martin and co-workers. 65 The coefficients k(r(Ag)/C ads (Ag + )-HyCOM-A(973)) and k(r(Ag)/C ads (Ag + )-P-25) were estimated to be 1.3 and 0.45, respectively, from the slope of the r(Ag + )-C ads (Ag + ) plot in Figure 6, presumably reflecting the recombination rate in the TiO 2 particles; the rate constant for e --h + recombination for HyCOM-A(973) was 2-2.5 times smaller than that for P-25, 63 which is almost consistent with the ratio of the coefficient k in this system. Thus, for each TiO 2 , the rate of the photocatalytic reaction, that is, photocatalytic activity, is governed by the amount of surfaceadsorbed substrate(s).…”
Section: Resultsmentioning
confidence: 94%
“…Many studies have been performed to obtain visible light activity by modification of titania with metal and non-metal elements [4][5][6][7]. The second limitation can be overcome by surface modification of titania with noble metals and their compounds that inhibit the charge recombination by increasing the transfer of photoexcited electrons from titania to substrates [5,[8][9][10]. Another approach is the preparation of p-n junction photocatalysts (e.g., nickel oxide/titania) to induce an internal electric field in the contact between p-type and n-type materials, which can increase e --h + separation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Electron paramagnetic resonance (EPR) has also been used to measure such species [4][5][6][7][8], though active oxygen species liberated simultaneously may interfere. Spectroscopy is an alternative way for investigation on the dynamics of electrons and positive holes, and ultrafast spectroscopy under various conditions has been reported [9][10][11][12][13]. In those spectroscopic studies, diffuse reflectance (DR) spectroscopy has been frequently employed to estimate absorption of powder samples, but sometimes scattering and reflection cause difficulty in accurate measurement of photoabsorption [14].…”
Section: Introductionmentioning
confidence: 99%